1998
DOI: 10.1007/s001130050307
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde intramedullary nailing in humeral fractures with new implants. Analyse of 120 consecutive cases

Abstract: Since 1993, 120 fractures of the humerus were treated by retrograde unreamed nailing. Operations were performed on simple, complex, compound and pathological fractures of the proximal three quarter of the humerus. On the proximal humerus, displaced two-part-fractures and occasionally three- or four-part-fractures were stabilized. In 110 cases a prototype of an unreamed humeral nail with deployable fins for proximal locking was employed. In another ten cases the new solid interlocking nail of the AO/ASIF was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…These findings are in agreement with those of several other authors [12, 13]. According to their mechanisms, the accidents can be divided into high-energy and low-energy trauma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with those of several other authors [12, 13]. According to their mechanisms, the accidents can be divided into high-energy and low-energy trauma.…”
Section: Discussionsupporting
confidence: 93%
“…Loitz and co-authors [12] found in their study on retrograde medullary nailing a value of 87 % for the unaffected side. In this patient cohort, the only gender-specific difference was the fact that female patients had on average a marginally better value by 2% on both sides.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder function was significantly worse after antegrade nailing [114]. With retrograde nailing, peri-articular ossification and adhesions in the elbow region disturbing elbow function, also have been described [21,35,38,84,105,113,115]. According to Faragos no sufficient arguments exist in favour of either way of introduction [41].…”
Section: Insertion Site Morbiditymentioning
confidence: 99%
“…Die Drahtwanderung wird von Hofmann et al [30] mit 21 % angegeben und ein sekundärer Repositionsverlust in 16 % der Fälle beobachtet. Retrograd eingebrachte Humerusnägel mit ausfahrbaren Krallen als Fixierung der proximalen Fraktur wiesen vergleichbare Implantatperforationen und sekundäre Fehlstellungen, wie die intramedulläre Zifko-Nagelung [54], insbesondere im osteoporotischen Knochen, auf. Retrograd eingebrachte Humerusnägel mit ausfahrbaren Krallen als Fixierung der proximalen Fraktur wiesen vergleichbare Implantatperforationen und sekundäre Fehlstellungen, wie die intramedulläre Zifko-Nagelung [54], insbesondere im osteoporotischen Knochen, auf.…”
Section: Subkapitale 2-segmentfrakturenunclassified